2020
DOI: 10.2337/dc20-1340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities and Glycemia at Admission and Dipeptidyl Peptidase 4 Inhibitors in Patients With Type 2 Diabetes With COVID-19: A Case Series From an Academic Hospital in Lombardy, Italy

Abstract: Diabetes may unfavorably influence the outcome of coronavirus disease 19 (COVID-19), but the determinants of this effect are still poorly understood. In this monocentric study, we aimed at evaluating the impact of type 2 diabetes, comorbidities, plasma glucose levels, and antidiabetes medications on the survival of COVID-19 patients. RESEARCH DESIGN AND METHODS This was a case series involving 387 COVID-19 patients admitted to a single center in the region of Lombardy, the epicenter of the severe acute respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 40 publications
(42 reference statements)
9
137
0
2
Order By: Relevance
“…study, patients with COVID-19 infection using insulin for treatment of DM were associated with poor prognosis compared to non-insulin users. [ 24 ] Consistent with our results , a recent study conducted in Lombardo found that treatment with insulin and lower lymphocyte count were associated with higher mortality, even after adjustment for sex and age, whereas the use of metformin or DPP-4 inhibitors were associated with a lower mortality rate [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…study, patients with COVID-19 infection using insulin for treatment of DM were associated with poor prognosis compared to non-insulin users. [ 24 ] Consistent with our results , a recent study conducted in Lombardo found that treatment with insulin and lower lymphocyte count were associated with higher mortality, even after adjustment for sex and age, whereas the use of metformin or DPP-4 inhibitors were associated with a lower mortality rate [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…Some of the enrolled patients had been already involved in other COVID-19 studies evaluating endpoints which were different from the present study [31][32][33][34][35].…”
Section: Methodsmentioning
confidence: 95%
“…In a retrospective case-control study from northern Italy, sitagliptin treatment during hospitalization was associated with reduced mortality and improved clinical outcomes in such patients 89 . Another Italian case series described the association between DPP4i treatment and a statistically significantly reduced mortality; however, this result was based on only 11 patients (of whom one died) 90 . However, DPP4i treatment was associated with worse outcomes (mortality results were not presented) in 27 patients with T2DM treated with DPP4is than in 49 treated with other glucose-lowering medications 87 .…”
Section: Dipeptidyl Peptidasementioning
confidence: 97%